The rise in Climate-Smart Agriculture strategies, policies, partnerships and investments across the globe - Dinesh, Dhanush; Aggarwal, Pramod K.; Khatri-Chhetri, Arun; Loboguerrero Rodriguez, Ana María; Mungai, Catherine; Radeny, Maren A.O.; Sebastian, Leocadio S.; Zougmoré, Robert B. (2017)
Since the term ‘climate-smart agriculture’ (CSA) was coined in 2010, a growth in strategies, policies, partnerships and investments in the area has been observed. Here we have summarised key CSA efforts globally and in South Asia, Southeast Asia, East Africa, West Africa, and Latin America. We have interpreted CSA in the broad sense, including efforts which may not mention CSA but implicitly contribute to CSA pillars. We note that many international and regional organisations, and countries, are implementing policies and programmes promoting and upscaling CSA. While the growth in strategies, policies, partnerships and investments is positive and creates a favourable enabling environment for CSA, these need to be complemented with targeted implementation on the ground, sustainable financing, institutional coordination and metrics to measure the efficacy of interventions.